Problems Associated with the Diagnosis of Imported Malaria in Anhui Province, China - Li, Weidong (Am J Trop Med Hyg, 2020)
Imported malaria in Anhui Province, China, remains a significant public health issue with frequent reporting of severe and fatal cases, partly because of globalization and increased international communication. A retrospective evaluation using surveillance data from 2012 to 2018 was conducted to draw lessons on diagnosis of imported malaria. Epidemiological characteristics, together with diagnostic information, were analyzed using descriptive and comparative statistics. Simultaneously, blinded rechecking of malaria blood slides was performed at general hospitals in Anhui Province in 2018. The results showed that, in their first medical visits, 238 (28.2%) of 844 imported cases were not correctly diagnosed. Notably, the proportion of patients who were misdiagnosed at the first clinic visit was 104/120 (86.7%) at private and village clinics, and 41/81 (50.6%) at primary hospitals. The species identification rates for Plasmodium falciparum, Plasmodium vivax, Plasmodium ovale, and Plasmodium malariae were 85.2%, 66.7%, 23.2%, and 32.3% (χ(2) = 224, P < 0.001), respectively. Nearly 7% of cases lacked laboratory evidence and were classified as presumed cases. Our findings suggest that physicians and health care providers, especially those at the primary level, lacked the awareness of diagnosing imported malaria. The training of physicians in malaria diagnosis needs to be enhanced. In addition, polymerase chain reactions (previously only carried out at the provincial level) should be performed at municipal CDC for rapid species identification, thereby guiding clinical treatment.